A Methodology Based on the Measurement of the Value Created by Library Institution and the Information Resources in Social Sciences and Humanities: Citation Analysis Findings - II - Oya Gürdal Tamdoğan (Türk Kütüphaneciliği)
The main focus of the article is to answer the question of how to evaluate the process of information production, which is being dwelled on lately in literatüre, in relation to national realities more sufficiently through citation analysis. In this respect, within the framework of the limitations of the study, the articles (296 articles, 7.804 citations) included in national and international bibliographic databases and the ones not included (191 articles and 4.620 citations) because of different reasons in the realities of country are evaluated in two different sets of data (1st and the 2nd set) and the acquired findings are presented. Therefore, in the study of citation analysis, 487 of12.424 articles are analyzed. However, one of the supposed facts which are foreseen at the beginning of the study is revealed that though 60,78% of the articles take place in bibliographic control resources, 39,21 % of the articles do not exist. In other words, 39,21% of the papers, which are qualified as the results of the information production process, is not available in both national and the international level. 1.085 citations (archive records, web sites etc.) out of 12.424 citations are not evaluated; because such references are not expected to exist in the library collection. In this direction, 11.339 citations are analyzed and investigated by their availability in the printed collections and accessibility in the e-collections of Ankara University libraries. 11.339 citations acquired from the articles of social sciences academic staff at Ankara University revealed the following results: 5.684 (50,14%) out of 11.339 citations are found (in printed/electronic/printed+e-collections). 3.333 (29,39%) of the citations are available in the printed collections. 2.351 (20,73%) of the citations are accessible in the e-collections.